Sikap Hidup Hamba Tuhan Berdasarkan 2 Timotius 2:1-13 - Iva Trifena Mayrina Wokas (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2021)
AbstractAttitude to life is fundamental in the life of God's servant. This attitude to life helps servants of God in maintaining the purity of their vocation and avoiding the temptations that exist. Paul wrote 2 Timothy 2: 1-13 as an advice to Timothy to keep his vocation pure and not be influenced by heresy that existed at that time. This research aims to find out the attitude of life in the text of 2 Timothy 2: 1-13 and to find out its implications for God's servants today. This research is a qualitative research with a grammatical historical approach. The attitude of life from the text of 2 Timothy 2: 1-13 is strong in grace, trustworthy, heeding the Word of God, following Jesus' example in enduring suffering and being patient in enduring suffering. By maintaining the attitude of life, a servant of God can be an example for others and also case reports to God's servants can be minimal. Abstrak Sikap hidup merupakan hal yang mendasar dalam kehidupan hamba Tuhan. Sikap hidup menolong hamba Tuhan dalam menjaga kemurnian panggilannya dan menghindarkan diri dari godaan yang ada. Paulus menuliskan surat 2 Timotius 2:1-13 sebagai nasihat kepada Timotius untuk menjaga kemurnian panggilannya dan tidak terpengaruh dengan ajaran sesat yang ada pada waktu itu. Penelitian ini bertujuan untuk menemukan sikap hidup dalam teks 2 Timotius 2:1-13 dan mencari implikasinya bagi hamba Tuhan pada masa kini. Penelitian ini merupakan penelitian kualitatif dengan pendekatan historikal gramatikal. Adapun sikap hidup dari teks 2 Timotius 2:1-13 adalah kuat dalam kasih karunia, dapat dipercaya, memperhatikan Firman Tuhan, mengikuti teladan Yesus dalam menanggung penderitaan dan sabar dalam menanggung penderitaan. Dengan menjaga sikap hidupnya seorang hamba Tuhan dapat menjadi teladan bagi orang lain dan juga berita kasus pada hamba Tuhan dapat minim terjadi.